2016
DOI: 10.1002/pssa.201532882
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of pulsed DC magnetron deposited Fe‐doped SnO2 coatings

Abstract: Iron-doped SnO 2 coatings were deposited in a 50 kHz DCpulsed magnetron sputtering discharge. The pulses had a duration of 4 ms in selected gas mixtures from pure argon up to 60% of oxygen at a constant total pressure of 0.2 Pa. A single target of SnO 2 with Fe inset was used. The mass spectrometry study detected the gas-related ions Ar þ , O 2 þ and O þ , where the last one becomes the dominant positive ion at higher oxygen contents. Atomic oxygen ions had a higher energy as it resulted from the collision-cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…A wide variety of growth methods can typically be used for the deposition of undoped and differently doped tin oxide thin films, including magnetron sputtering [20,21,22,23], molecular beam epitaxy [24], pulsed-laser deposition (PLD) [25], chemical vapor deposition (CVD) [26], atomic layer deposition (ALD) [27], or spray pyrolysis [28,29,30]. Spray pyrolysis has the advantages of being cost efficient and surface scalable [31].…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of growth methods can typically be used for the deposition of undoped and differently doped tin oxide thin films, including magnetron sputtering [20,21,22,23], molecular beam epitaxy [24], pulsed-laser deposition (PLD) [25], chemical vapor deposition (CVD) [26], atomic layer deposition (ALD) [27], or spray pyrolysis [28,29,30]. Spray pyrolysis has the advantages of being cost efficient and surface scalable [31].…”
Section: Introductionmentioning
confidence: 99%
“…The layer morphology was also determined by means of atomic force microscopy (AFM) and transimission electron mircoscopy (TEM) measurements. These measurements are reported in [ 18 19 ]. It was found that the intended layer structure (glass-gold-SnO x ) was achieved and the surface roughness is low (root mean square average of height deviation R q < 0.2 nm).…”
Section: Methodsmentioning
confidence: 99%
“…With the development of electroplating technology and nanotechnology, the research on nanocomposite coatings has become the focus of domestic and foreign scholars. The introduction of second-phase particles enhances the performance of these coatings, such as nano-scale SiO 2 [21], SnO 2 [22], Al 2 O 3 [23][24][25][26], TiO 2 [27], SiC [28], PTFE [29], ZrO 2 [30], graphene [31,32], etc. The phase distribution in the nanostructured coating is more uniform than that in micron structure coating since the atoms in the matrix are more firmly bound to the nano reinforcement; the nano-enhancing phase has a more significant enhancement effect than the micron size in the metal system.…”
Section: Introductionmentioning
confidence: 99%
“…On the flip side, the powder tends to agglomerate during the plating process, and it isn't easy to uniformly grow on the substrate surface. To solve this bad agglomeration phenomenon, the sol-gel method can be used to enhance the coating properties [33], e. g., SnO 2 sol [22], TiO 2 sol [34], and SiO 2 sol [35].…”
Section: Introductionmentioning
confidence: 99%